THE WAY OF LIFE AND TRADE RELATIONS OF THE INHABITANTS OF THE TOWNS AND VILLAGES OF BUKHARA IN THE MIDDLE AGES (American Journal of Research in Humanities and Social Sciences, 2023)
This article talks about the role of Bukhara in the life of medieval states, especially in The Times of the Khwarazmshahs, about socio-economic relations in Bukhara, its rise and the development of Applied Arts, construction spheres.